The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar - Chakrabarty, Prosanta; Ng, Heok Hee (Zootaxa, 2005)
The identity of South Asian riverine bagrid catfishes usually referred to as Mystus cavasius (Hamilton, 1822) is reviewed. Three species comprise what is currently understood as M. cavasius: M. cavasius s. str. from northern India, M. seengtee from southern India and a new species, M. falcarius, from the Salween and Irrawaddy river drainages in Myanmar and the shorter river drainages in southern Myanmar. Mystus seengtee is resurrected from synonymy with M. cavasius and both species are redescribed. The three species differ from other congeners with a long-based adipose fin in having a combination of a black spot in front of the dorsal-spine base, a dark humeral mark, a body without distinct midlateral stripes, very long maxillary barbels reaching to caudal-fin base, dorsal spine short and feebly serrate, tall dorsal fin, and 13ñ29 gill rakers. These species differ from each other in dorsal fin shape, shape of the predorsal profile, coloration, and number of rakers on the first gill arch.